2021
DOI: 10.2196/25541
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to Remote Clinic Visits in a Smoking Cessation Trial During the COVID-19 Pandemic: Mixed Methods Evaluation

Abstract: Background:The pandemic of SARS-CoV-2, which causes COVID-19, has caused disruptions in ongoing clinical trials and is expected to accelerate interest in conducting research studies remotely.Objective: A quasi-experimental, mixed methods approach was used to examine the rates of visit completion as well as the opinions and experiences of participants enrolled in an ongoing clinical trial of smoking cessation who were required to change from in-person clinic visits to remote visits using video or telephone conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Very few participants took up the option of video calls; however, given that the service was offered in the earlier stages of the pandemic, it is possible that, as has been seen by local services [5], increasing confidence in video call technology would have seen greater uptake with time. Many participants identified building a relationship with a single allocated SCP was key to making a successful quit attempt, which may be more important than the choice of virtual platform [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few participants took up the option of video calls; however, given that the service was offered in the earlier stages of the pandemic, it is possible that, as has been seen by local services [5], increasing confidence in video call technology would have seen greater uptake with time. Many participants identified building a relationship with a single allocated SCP was key to making a successful quit attempt, which may be more important than the choice of virtual platform [11].…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 systematic review found moderate-certainty evidence that proactive telephone counselling helps smokers to quit smoking, but insufficient evidence to assess whether telephone counselling provided as an adjunct to other smoking cessation therapies has any additional effect [9]. There are promising signs that remote cessation services operated with some success in the pandemic; for example, studies required to change interventions from faceto-face behavioural support to remote behavioural support due to the pandemic found that quit rates [10] and clinic visits [11] for those in the intervention arm were similar for face-to-face and remote delivery. In Canada, it was found that the move to phone-based care for smoking cessation for cancer patients during the COVID-19 pandemic sometimes decreased counselling interruptions and improved follow-up rates [7].…”
Section: Global Smoking Cessation Services In Covid-19 Pandemicmentioning
confidence: 99%
“…While remote trials may alleviate structural barriers by allowing flexibility based on personal availability, TestBoston participants highlighted work and family obligations, time, and scheduling constraints that conflicted with sample return, as significant barriers. Other potential gaps that have been described include technology access, literacy and privacy concerns that may be unaddressed, and at worst, exacerbated by remote models [ 14 , 40 43 ]. We attempted to mitigate these factors by providing translation services, intense participant support, and participant-informed adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…In a mixed-methods analysis, Mahoney et al [31] concluded that although the transition was not thoroughly planned but in many cases improvised to deliver phone or video call counseling, it contributed to keep the rates of appointments and collection of saliva samples at the same level as before the pandemic. During the lockdown, participants attended 83.6% of their remote visits and returned 93.2% of the saliva samples.…”
Section: Tobaccomentioning
confidence: 99%